1988
DOI: 10.1093/infdis/158.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Human Disease Due to Mycobacterium smegmatis

Abstract: Mycobacterium smegmatis is a rapidly growing environmental species not considered a human pathogen. We identified 22 human isolates of M. smegmatis from Australia and the southern United States: 19 were from skin or soft-tissue infections, and none were from urine or the male genital tract. These isolates closely resembled Mycobacterium fortuitum, except for a negative three-day arylsulfatase test; growth at 43-45 C; a low semiquantitative catalase test; and, in 50% of isolates, a late-developing, yellow-to-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
0
5

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 27 publications
7
124
0
5
Order By: Relevance
“…In 1986 Vonmoos et al [138] reported the first case of pleuropulmonary disease caused by M. smegmatis. Wallace and co-workers [139] identified 22 additional human isolates of M. smegmatis from Australia and the southern United States: 19 were from skin or soft-tissue infections, and none were from urine or the male genital tract.…”
Section: Ulcerans This Organism Was First Isolated In 1948mentioning
confidence: 99%
“…In 1986 Vonmoos et al [138] reported the first case of pleuropulmonary disease caused by M. smegmatis. Wallace and co-workers [139] identified 22 additional human isolates of M. smegmatis from Australia and the southern United States: 19 were from skin or soft-tissue infections, and none were from urine or the male genital tract.…”
Section: Ulcerans This Organism Was First Isolated In 1948mentioning
confidence: 99%
“…In contrast, there were 33 nonrespiratory isolates, approximately two-thirds of which were known to be clinically significant. The most common types of clinical disease associated with the MCLO were posttraumatic wound infections and catheter-related sepsis, which are clinical diseases that are relatively commonly caused by members of other taxonomic groups of rapidly growing mycobacteria (3,(22)(23)(24)27). Extensive growth and biochemical analyses of the 87 MCLO isolates revealed that they were fairly homogeneous and had characteristics similar to those described 10 years earlier (2, 17), except that they exhibited variable nitrate reduction reactions (45%) ( Table 1).…”
mentioning
confidence: 99%
“…Only 9 cases of infection caused by M. wolinskyi have been reported (1)(2)(3), and these included 3 cases of bone infection and 1 case of infection of a hip prosthesis. All patients had a history of surgery after traumatic injury and all specimens were isolated from the surgical wound.…”
Section: Bacteremia Caused By Mycobacterium Wolinskyimentioning
confidence: 99%